2015
DOI: 10.5465/amj.2011.0934
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Trust Outcomes from Exchange Relationships: Social Exchange and Learning Benefits of Prior Ties in Alliances

Abstract: Social exchange theory is a broad theory that has been used to explain trust as an outcome of various exchange relationships, and research commonly presumes trust exists between exchange partners that have prior relationships. In this paper, we contribute to research on social exchange theory by isolating the trust outcomes of interorganizational exchanges from other outcomes emphasized by learning and knowledge-based perspectives, and by specifying important boundary conditions for the emergence of trust in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 105 publications
3
113
0
2
Order By: Relevance
“…Different from the traditional “rivalrous view” of competitive dynamics, which highlights a firm‐centric perspective (Chen & Miller, ), the “relational” view emphasizes the necessity of understanding others’ needs and preferences, as well the interdependencies between self and others, before deciding on competitive moves. Our research extends this line of argument by suggesting that firms can increase their “relational” savvy through learning in various forms of interactions, including alliances (Lioukas & Reuer, ), competitions (Tsai, Su, & Chen, ), and the transition between the two; all of these relationships may inform subsequent competitive encounters.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Different from the traditional “rivalrous view” of competitive dynamics, which highlights a firm‐centric perspective (Chen & Miller, ), the “relational” view emphasizes the necessity of understanding others’ needs and preferences, as well the interdependencies between self and others, before deciding on competitive moves. Our research extends this line of argument by suggesting that firms can increase their “relational” savvy through learning in various forms of interactions, including alliances (Lioukas & Reuer, ), competitions (Tsai, Su, & Chen, ), and the transition between the two; all of these relationships may inform subsequent competitive encounters.…”
Section: Discussionsupporting
confidence: 59%
“…Second, repeated collaborations restrain a firm’s incentive to compete by improving the effectiveness of formal governance mechanisms, such as contracts, in preventing opportunistic learning in exploratory activities. Repeated ties help firms learn how to work together effectively by helping them discover their partners’ self‐serving behaviors and patterns, which in turn leads them to anticipate similar behavior in the future (Doz, ; Lioukas & Reuer, ). Firms normally incorporate such knowledge into improving their contracts and other defensive mechanisms to guard against competitive behaviors from the same partners (Mayer & Argyres, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Past research has explored various theoretical mechanisms linking prior collaborations with a focal partnership's performance. Studies in the entrepreneurial finance, networks, and strategic alliance literatures have argued that prior collaborations between partners improve current partnership performance by fostering relationship continuity, mutual learning, facilitating trust, and triggering the development of collaborative capabilities, norms, and routines (Coleman, ; Gulati, ; Lioukas & Reuer, ). Other studies, however, have suggested that there are limits to the benefits conferred by prior collaborations, which can lead to increasing resource redundancy, overconfidence, and inertia (Li & Rowley, ; Uzzi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exchange secures outcomes for all parties involved that is founded on mutually rewarding transactions (Malmström and Johansson, 2016). Considering this, Lioukas and Reuer (2015) argue that the theory of social exchange is founded on the reciprocity belief. This belief is the departing argument for social exchange theory from an internal marketing perspective seeing that both the organisation and the employee has a responsibility to recompense for benefits received.…”
Section: Theories Grounding the Studymentioning
confidence: 99%